Conductive paste and conductive film formed using the same

By using low-temperature melt tin alloy and non-tin alloy conductive filler in conductive adhesives to form conductive paths, the problem of insufficient conductivity of conductive films in the prior art is solved, and high conductivity and protection of organic semiconductor equipment are achieved.

JP7656862B2Active Publication Date: 2025-04-04PANASONIC INTELLECTUAL PROPERTY MANAGEMENT CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2021101683
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-06-18
Publication Date
2025-04-04
Estimated Expiration
2041-06-18

AI Technical Summary

Technical Problem

In the prior art, the conductive film formed by a conductive adhesive made of conductive filler such as Ag or carbon has a large resistance to the conductive path formed by the conductive particles when point contact, resulting in insufficient conductivity of the conductive film.

Method used

The conductive adhesive is used, which consists of conductive particles of a low-temperature melt tin alloy (melting point 120°C or below), conductive fillers of non-tin alloys, active agents that remove the conductive particle oxide film and indefinite solvents, and melt the conductive particles during heating to form a conductive path.

Benefits of technology

By combining low-temperature melt tin alloy and non-tin alloy conductive filler, conductive paths are formed, which significantly reduces the resistance of the conductive film and improves the conductivity, while avoiding chemical or physical damage to organic semiconductor equipment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007656862000001
    Figure 0007656862000001
Patent Text Reader

Abstract

To provide a conductive paste from which a low-resistance conductive film can be formed without necessity of any vacuum device such as that for vapor deposition or spattering.SOLUTION: A conductive paste includes: solder powder whose melting point is equal to or lower than 120°C; a conductive filler; a flux eliminating an oxide film of the solder powder; and a solvent. With respect to the mass ratio of the conductive filler to the solder powder, the mass of the conductive filler accounts for 20-80 mass% of the mass of the solder powder. Melted solder powder is not formed into a spherical shape even when the temperature of the solder powder becomes its melting point or higher because the conductive paste contains particles of the conductive filer not composed of solder powder, so that solder gets into spaces among conductive particles and thereby conductive paths are formed.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a conductive film that can be used as an electrode for, for example, a semiconductor device, and a conductive paste for forming the same. [Background technology]

[0002] In organic semiconductor devices such as organic electroluminescence devices, organic thin-film solar cells, and organic field-effect transistors, Au is often used in conductive films as electrodes, taking into consideration the advantages of conductivity, stability, etc. Au films can be formed by dry processes using vacuum equipment such as deposition and sputtering, or wet processes such as plating.

[0003] However, when an Au film is formed by such a method, the cost of film formation is high in terms of materials and processes. Therefore, various methods that do not use a vacuum device have been investigated as a cheaper conductive film formation method, in which a conductive paste composed of Ag, conductive filler such as carbon, and a binder is applied by printing, coating, etc., and then heated and cured to form a conductive film (see, for example, Patent Document 1 below). [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2020-140964 A Summary of the Invention [Problem to be solved by the invention]

[0005] As described above, when a conductive film is formed using a conductive paste composed of conductive fillers such as Ag and carbon, conductive particles that are in point contact with each other form a conductive path, and the resistance of the point contacts between such conductive particles becomes large, so that it becomes a challenge to further improve the conductivity of the conductive film.

[0006] The present invention has been made in consideration of these problems, and aims to provide a conductive paste that forms a conductive film with excellent conductivity in a method of forming a conductive film using a conductive paste without requiring a vacuum device. [Means for solving the problem]

[0007] As a result of intensive research into the above-mentioned problems, in a first aspect, the present invention provides a new conductive paste. This conductive paste comprises: (1) Solder powder having a melting point of 120°C or less; (2) a conductive filler; (3) Flux to remove the oxide film from the solder powder; (4) Solvent The mass ratio of the conductive filler to the solder powder is 20 to 80%.

[0008] In a preferred embodiment, in the conductive paste of the present invention, the solder powder and the conductive filler have an average particle size of 20 μm or less.

[0009] In a preferred embodiment, in the conductive paste of the present invention, the solder powder is composed of a solder alloy containing In.

[0010] In a preferred embodiment, in the conductive paste of the present invention, the conductive filler is a Cu, Ag or carbon filler, or may be any mixture of these fillers. In another preferred embodiment, the conductive filler may include at least one selected from Cu, Ag and carbon, and at least one other conductive component (e.g., Au, Sn, Ni, etc.) that may be used as needed.

[0011] In a preferred embodiment, in the conductive paste of the present invention, the ratio of the combined mass of the solder powder and conductive filler to the combined mass of the solder powder, conductive filler, flux and solvent (i.e., when the conductive paste does not contain any components other than these components, this corresponds to the total mass of the conductive paste) is 20 to 60%.

[0012] In a preferred embodiment, in the conductive paste of the present invention, the solvent is a non-polar organic compound that is liquid at room temperature (about 25° C.) and is composed of C (carbon), H (hydrogen), and optionally other elements (e.g., oxygen, nitrogen, etc.), and the flux is an organic acid that is solid at room temperature. It is particularly preferred that this organic acid be in the form of a powder.

[0013] In a second aspect, the present invention provides a conductive film formed using the conductive paste of the present invention described above or below.

[0014] In a third aspect, the present invention provides a method for forming, i.e., a manufacturing method of, the conductive film of the present invention, which includes applying the conductive paste of the present invention to an object (e.g., an organic semiconductor device) to form a layer of the conductive paste, and heating the layer of the conductive paste to a temperature equal to or higher than the melting point of the solder powder, preferably at least 20° C. higher than the melting point, to form a conductive film. Effect of the Invention

[0015] The conductive paste of the present invention combines solder powder with a melting point of 120°C or less as conductive particles with a non-solder conductive filler. When the conductive paste contains only solder powder, the solder powder melts and becomes spherical when the paste is heated above its melting point. As a result, the conductive film formed contains such spherical solder in the conductive path, and may not function adequately as a conductive film.

[0016] By including particles of a conductive filler other than solder powder in the conductive paste of the present invention, the molten solder powder does not become spherical even when the conductive paste reaches a temperature equal to or higher than the melting point of the solder powder, and the solder penetrates between the conductive particles to form a conductive path, thereby ensuring sufficient conductivity of the conductive film.

[0017] In the conductive paste of the present invention, the solvent contained in the solder paste is C (carbon). 、When the organic acid acting as a flux is non-polar and composed of H (hydrogen) and possibly other elements, and is a solid powder at room temperature, even if the conductive paste of the present invention is applied (e.g., painted) to the surface of an organic semiconductor device, a conductive film can be formed in a state in which the organic material constituting the organic semiconductor device is not easily adversely affected by the conductive paste (e.g., destruction of the semiconductor device due to chemical actions (e.g., chemical reactions) and / or physical actions (e.g., dissolution) caused by solvents and flux). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0018] Hereinafter, embodiments of the conductive paste of the present invention will be described in detail.

[0019] (solder powder) The solder powder contained in the conductive paste of the present invention is composed of a solder alloy having a melting point of 120°C or less. Therefore, the solder powder has a melting point of 120°C or less. Such solder powder is a particle composed of a solder alloy having a melting point of 120°C or less, which is called a low-temperature solder. If the melting point of the solder powder exceeds 120°C, a problem may occur in that the characteristics of the organic semiconductor device deteriorate. In addition, from the viewpoint of reliability in the operating environment, the melting point of the solder powder is preferably 80°C or more.

[0020] Specifically, the solder powder is preferably a solder alloy containing at least one metal selected from indium, tin, and bismuth. More specifically, the solder alloy may be composed of only such a metal, or may be composed of such a metal and at least one other metal (e.g., copper, silver, zinc, etc.).

[0021] The solder alloy constituting the solder powder used in the conductive paste of the present invention may be, for example, at least one solder alloy selected from the group consisting of Sn-In, Sn-Bi-In, Bi-In, Sn-Ag, Sn-Ag-Cu, Sn-Ag-In, Sn-Cu-In, Sn-Ag-Cu-In, and Sn-Ag-Cu-Bi-In. That is, these solder alloys may be used alone or in combination of two or more of these solder alloys. Particularly preferred solder alloys are, for example, Sn-In and Sn-Bi-In. At least two of these various solder powders may be used in combination.

[0022] In a preferred embodiment, the solder powder may be in any suitable microscopic form, for example, granular (may be spherical), thin (flake) form, etc. The microscopic particles constituting the solder powder preferably have an average particle diameter of 20 μm or less, more preferably an average particle diameter of 0.5 to 15 μm. If the average particle diameter is larger than this range, the conductive film may become thicker, resulting in a problem of higher costs, while if it is smaller than this range, the melting property of the solder may deteriorate.

[0023] The average particle size referred to in this specification means "the volume cumulative particle size D50 measured by a laser diffraction scattering type particle size distribution measuring device."

[0024] (Conductive filler) The conductive filler contained in the conductive paste of the present invention has a melting point at which it does not melt when the conductive paste is heated to melt the solder powder. Preferably, the melting point of the conductive filler is 200°C or higher. If the melting point is less than 200°C, excessive heating of the conductive paste may cause a problem that the conductive filler melts. The conductive filler, like the solder powder, may be in any suitable form of minute matter, for example, granular (may be spherical), flake-like, minute granular, thin (flake-like), or amorphous lump-like matter. Examples of such conductive materials include metals (e.g., Cu, Ag, Ni, Au, alloys of at least one of these metals with other metals, etc.), and carbon (e.g., carbon black, graphite, nanocarbon, etc.). Particularly preferred conductive fillers include granular (e.g., spherical) minute matter composed of Cu and Ag. At least two of these various conductive fillers may be used in combination.

[0025] In another embodiment, the conductive filler may be a micro-object having a coating of the above-mentioned conductive material, i.e., a composite micro-object. For example, the conductive filler may be a Cu filler having a Au coating on the surface.

[0026] In a preferred embodiment, the minute particles constituting the conductive filler preferably have an average particle diameter of 20 μm or less, more preferably an average particle diameter of 0.5 to 15 μm. The "average particle diameter" of the conductive filler mentioned here is used in the same sense as in the case of the solder powder.

[0027] In the conductive paste of the present invention, with respect to the mass ratio of the solder powder to the conductive paste, the ratio of the mass (B) of the conductive filler contained in the conductive paste to the mass (A) of the solder powder contained in the conductive paste (i.e., B / A) is 20 to 80%, preferably 30 to 50%.

[0028] If the thickness is smaller than the range, the amount of solder powder connecting the conductive fillers in the conductive film is insufficient, and a part of the conductive path is formed by point contact between the conductive particles, which tends to result in insufficient conductivity of the conductive film that is formed. If the thickness is larger than the range, the amount of solder powder that solidifies in a spherical shape without connecting the conductive fillers in the conductive film increases, which tends to result in insufficient conductivity of the conductive film that is formed.

[0029] (Flux) The flux contained in the conductive paste of the present invention has a reducing power capable of removing an oxide film on the surface of an object to which the conductive paste is applied (i.e., an adherend, for example, an organic semiconductor device), an electrode of the object, a solder powder, and / or a conductive filler. For example, an organic acid, an amine halogen salt, an amine organic acid salt, etc. are used as the flux.

[0030] Examples of organic acids include saturated aliphatic monocarboxylic acids such as lauric acid, myristic acid, palmitic acid, and stearic acid; unsaturated aliphatic monocarboxylic acid such as crotonic acid; saturated aliphatic dicarboxylic acids such as oxalic acid, L(-)-malic acid, malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, and sebacic acid; unsaturated aliphatic dicarboxylic acids such as maleic acid and fumaric acid; aromatic carboxylic acids such as phthalaldehyde acid, phenylbutyric acid, phenoxyacetic acid, and phenylpropionic acid; ether dicarboxylic acid such as diglycolic acid, and other organic acids such as abietic acid and ascorbic acid.

[0031] Examples of amine halogen salts include amine hydrochlorides such as ethylamine hydrochloride, diethylamine hydrochloride, dimethylamine hydrochloride, cyclohexylamine hydrochloride, triethanolamine hydrochloride, and glutamic acid hydrochloride; and amine hydrobromides such as diethylamine hydrobromide and cyclohexylamine hydrobromide.

[0032] Examples of the amine organic acid salts include propylamine, butylamine, hexylamine, heptylamine, triethanolamine, and mixtures with adipic acid, diethylglutaric acid, glutaric acid, succinic acid, and malonic acid.

[0033] The flux may be liquid or solid at room temperature, and at least two of the above-mentioned components may be used in combination. In order to prevent the target to which the conductive paste is applied, more specifically at least a part of the target to which the conductive paste is applied, for example, the organic material part of the target organic semiconductor device, from being affected by the flux contained in the applied conductive paste (for example, the flux contained in the conductive paste dissolves the organic material), the flux may be solid at room temperature, and in a particularly preferred embodiment, may be powdered.

[0034] (solvent) In a preferred embodiment, the solvent contained in the conductive paste of the present invention may be a non-polar organic compound, such as a hydrocarbon, an alcohol, an amide, etc., and examples thereof include alcohols (2-propanol, 1-butanol, 2-butanol, hexanol, 1,2-propanediol, heptanol, cyclohexanol, etc.), glycol ethers (ethylene glycol monobutyl ether, diethylene glycol monomethyl ether, etc.), aromatic hydrocarbons (xylene, etc.), aliphatic hydrocarbons (dodecane, decane, nonane, octane, p-menthane, etc.), amides (dimethylformamide, dimethylacetamide, dimethylsulfoxide, etc.), and others (N-methylpyrrolidone, siloxane, etc.). Two or more of these may be combined.

[0035] In order to prevent the object to which the conductive paste is applied, more particularly at least a portion of the object to which the conductive paste is applied (e.g., the organic material portion of an organic semiconductor device as the object), from being affected by the solvent contained in the applied conductive paste (e.g., the solvent contained in the conductive paste dissolves the organic material), it is particularly preferable that the solvent is inert to the object to which it is applied (has substantially no adverse effect).

[0036] For example, when the subject on which the conductive film is to be formed is an organic semiconductor device, the solvent is preferably one that does not substantially dissolve the organic material of the organic semiconductor device, and it is particularly desirable to use, for example, aliphatic hydrocarbons as the solvent.

[0037] (Other ingredients) In one preferred embodiment, the conductive paste of the present invention may contain other components as necessary. For example, the conductive paste may have a resin component that functions as a binder, which can improve the adhesion of the conductive film to the target and the flex resistance of the conductive film. As the resin component, for example, a cellulose derivative, polyvinyl acetal, polyester, etc. can be used. A cellulose derivative is more preferred.

[0038] In another preferred embodiment, the conductive paste of the present invention may contain other components as necessary. Such other components may include a thixotropic agent for controlling viscosity. By including such a component, the application stability of the paste is improved.

[0039] The conductive film of the present invention can be formed by applying the above-mentioned conductive paste of the present invention to an object such as an organic semiconductor device, for example by coating, to form a layer of conductive paste, and then heating the layer of conductive paste to a temperature equal to or higher than the melting point of the solder powder, preferably to a temperature at least 20°C higher than the melting point, and more preferably to a temperature at least 40°C higher. EXAMPLES

[0040] [Examples and Comparative Examples] Example 1 As an example, a conductive paste of the present invention was prepared using the following materials, and the resistance value of a conductive film formed by applying the paste to a glass plate was evaluated. Solder powder of 25Sn-55Bi-20In (melting point 96°C) with an average particle size of 10 μm (based on volume cumulative particle size D50 measured by a laser diffraction scattering type particle size distribution measuring device) was used. Cu powder with an average particle size (based on the volume cumulative particle size D50 measured by a laser diffraction scattering type particle size distribution measuring device) of 5 μm was used as the conductive filler. Glutaric acid was used as a flux. p-Menthane was used as the solvent.

[0041] To 57 parts by weight of p-menthane, 8 parts by weight of glutaric acid, 27 parts by weight of solder powder, and 8 parts by weight of Cu powder were added, and the mixture was kneaded for 10 minutes in a vacuum planetary mixer to obtain a conductive paste of Example 1.

[0042] A 100 μm thick polyimide tape was attached to both edges of a 1 mm thick glass slide, and the conductive paste was applied between the tapes. The conductive paste layer (100 μm thick) was then applied to the glass slide by flattening the paste along the top surface of the polyimide tape with a squeegee. The glass slide was heated on a hot plate set at 120°C for 5 minutes to form a conductive film.

[0043] The resistance of the conductive film formed was evaluated by measuring the resistance at a distance of 1 cm using a tester. A resistance value of less than 10 Ω was evaluated as "pass" (◯), and a resistance value of 10 Ω or more was evaluated as "fail" (×).

[0044] The resistance value of the conductive film formed using the conductive paste of Example 1 was 0.4Ω, and was evaluated as pass.

[0045] (Examples 2 to 7 and Comparative Examples 1 to 3) Similarly to Example 1, various conductive pastes of Examples 2 to 7 and Comparative Examples 1 to 3 were prepared, and the resistance value of the conductive film formed in the same manner as described above was evaluated. The amount of solder powder and the amount of Cu powder used in preparing the conductive pastes of the Examples and Comparative Examples, and the evaluation results are shown in Table 1 below. In addition, in all of the Examples and Comparative Examples, the amount of p-menthane was 57 parts by weight, and the amount of glutaric acid was 8 parts by weight.

[0046] [Table 1]

[0047] Comparing the results of Examples 1 to 7 with those of Comparative Examples 1 to 3, the resistance values ​​of the conductive films formed using the conductive pastes of the Examples in which the ratio C (=B / A) of the mass of Cu powder (B) to the mass of solder powder (A) is 20 to 80% are all evaluated as pass. It is considered that the conductive films in these Examples show low resistance values ​​because the molten solder connects the particles of Cu powder. However, when the ratio of Cu powder is too high as in Comparative Example 3, the amount of molten solder connecting the particles of Cu powder is insufficient, and the resistance value becomes high. On the other hand, when the ratio of Cu powder is too low as in Comparative Examples 1 and 2, the ratio of molten solder not effectively connecting the particles of Cu powder and agglomerating increases, which is considered to result in a non-uniform conductive film being formed and a high resistance value.

[0048] Furthermore, when the combined mass of the solder powder and the conductive filler is 20-60%, preferably 30-50%, of the total mass of the conductive paste (=A+B+p-menthane mass+glutaric acid mass), the resistance value of the formed conductive film meets the target (less than 10Ω); however, when the ratio D of the combined mass of the solder powder and the conductive filler to the mass of the conductive paste is too small as shown in Comparative Example 4, the amount of conductive components (i.e., solder and Cu) is insufficient, resulting in a high resistance value. Conversely, when the ratio D of the combined mass of the solder powder and the conductive filler is too large, exceeding 60%, as in Comparative Example 5, the viscosity of the conductive paste increases, and the coating property deteriorates, making it impossible to form a uniform conductive film. [Industrial Applicability]

[0049] The conductive paste of the present invention has the property that it can form a conductive film with excellent conductivity simply by applying it to a target by, for example, coating, and then heating it at a relatively low temperature, and is useful when forming a conductive film to be formed on an organic semiconductor device such as an organic EL device, an organic thin-film solar cell, an organic field effect transistor, etc. Moreover, it has the advantage that the conductive film can be formed without requiring a vacuum device.

Claims

1. A solder powder having a melting point of 120° C. or less; A conductive filler; Flux to remove the oxide film from the solder powder; Solvent and A conductive paste comprising at least The ratio of the mass of the conductive filler to the mass of the solder powder is 20 to 80%; A conductive paste, characterized in that the ratio of the combined mass of the solder powder and the conductive filler to the combined mass of the solder powder, the conductive filler, the flux and the solvent is 20 to 60%.

2. 2. The conductive paste according to claim 1, wherein the solder powder and the conductive filler each have an average particle size of 20 [mu]m or less.

3. 3. The conductive paste according to claim 1, wherein the solder powder contains In.

4. 4. The conductive paste according to claim 1, wherein the conductive filler is a filler of Cu, Ag or carbon.

5. 5. The conductive paste according to claim 1, wherein the solvent is a non-polar solvent composed of carbon and hydrogen, and the flux is a powder of an organic acid that is solid at room temperature.

6. A conductive film formed using the conductive paste described in any one of claims 1 to 5.

Citation Information

Patent Citations

  • Method of manufacturing semiconductor device

    JP2008109009A

  • Curable composition and connection structure

    JP2015180749A

  • Conductive paste and conductive laminate

    JP2020140964A

  • Metal paste for joining, method for manufacturing joined body, and joined body

    JP2021063262A